(untitled) - Sutcliffe, Andrea (New Jersey , NJ., 2002)
Follow the Ring of Fire from New Zealand to South America. Navigate the Blue Nile and walk the Great Wall of China. Meet the first person to reach the South Pole and witness the "Green Revolution" in India. Explore the people, landscapes, and languages of our fascinating planet and uncover the answers to all your questions about world geography . . .How old is the earth? See page 8.Can volcanoes form underwater? See page 14.What are maquiladoras? See page 50.Why are rain forests so important? See page 63.Where and what are the Pillars of Hercules? See page 77.Is the Red Sea really red? See page 88.What languages are spoken in Africa? See page 112.Do any plants or animals live in Antarctica? See page 133.
Keywords: Geography,Children’s questions and answers; Miscellanea,Juvenile literature